MENGATASI KESULITAN BELAJAR MELALUI KONSELING BEHAVIORISTIK DENGAN TEKNIK OPERANT CONDITIONING PADA SISWA KELAS VIII SMP N 3 BAE KUDUS - Naela Rif'atul Khasnak; Arista Kiswantoro; Sumarwiyah Sumarwiyah (Universitas Muria Kudus, 2022)
The purpose of this research is to: 1. To find the factors that cause Class VIII SMP N 3 Bae students to have learning difficulties. 2. To find out whether the application of behavioristic counseling with operant conditioning techniques is effective to overcome learning difficulties in class VIII SMP N 3 Bae. The type of research used is a Case Study. The subjects studied were class VIII SMP N 3 Bae Academic Year 2021/2022 who had learning difficulties. The independent variable in this study was behavioristic counseling using the Operant Conditioning technique, while the dependent variable was learning difficulties. Data collection techniques using Observation, Interview and Documentation techniques. Analysis of the data used is a qualitative data analysis. Based on the results of the study, it can be concluded that after being given Behavioristic Counseling with the Operant Conditioning technique, the counselee is able to change his behavior that makes learning difficulties, namely students can pay attention to the teacher while teaching, do not chat alone with friends, collect assignments on time, and study diligently every day.